Influence of Fluid Inflow Rate on Performance Effectiveness of Shell and Tube Type Heat Exchanger - Adinda Shalsa Bellabunda Wardhani; Alifta Titania Labumay; Erlinda Ningsih (Mechanical Engineering Department - Institut Teknologi Adhi Tama Surabaya, 2022)
In industrial processes, heat exchangers are needed to transfer a certain amount of heat energy from the system to the environment. The research object observed using a heat exchanger type 1- 2 shell and a tube was water in hot and cold fluids. It aimed to determine the relationship between hot and cold fluids and the heat transfer coefficient, fouling factor, and tool efficiency. The research method varied the hot water by 50, 70, 90, 100 mL/s and the cold water by 20, 40, 60, 80 mL/s. After getting the data for each fluid's inlet and outlet temperatures, the effectiveness analysis was calculated. The research results on the hot fluid variable demonstrated that the more the fluid was flowing into the shell, the higher the heat transfer coefficient, heat transfer velocity, and average effectiveness. Meanwhile, the fouling factor tended to decrease along with the increasing hot fluid. The cold fluid variable, the higher the cold fluid flows into the tube, the higher the heat transfer coefficient and the average heat transfer velocity. Furthermore, the fouling factor and effectiveness tended to decrease along with the increasing cold fluid flow.